Critical role of androgen receptor level in prostate cancer cell resistance to new generation antiandrogen enzalutamide - Hoefer, Julia; Akbor, Mohammady; Handle, Florian; Ofer, Philipp; Puhr, Martin; Parson, Walther; Culig, Zoran; Klocker, Helmut; Heidegger, Isabel (Oncotarget, 2016)
Enzalutamide is an androgen receptor (AR) inhibitor approved for therapy of metastatic castration resistant prostate cancer. However, clinical application revealed that 30 to 40% of patients acquire resistance after a short period of treatment. Currently, the molecular mechanisms underlying such resistances are not completely understood, partly due to a lack of model systems. In the present study we established three different cellular models of enzalutamide resistance including a cell line with wild type AR (LAPC4), DuCaP cells which overexpress wild-type AR, as well as a cell which has been adapted to long term androgen ablation (LNCaP Abl) and harbors the AR T878A mutation. After 10 months of cultivation, sustained growth in the presence of enzalutamide was achieved. When compared to controls, resistant cells exhibit significantly decreased sensitivity to enzalutamide as measured with 3[H]thymidine incorporation and WST assay. Moreover, these cell models exhibit partly re-activated AR signaling despite presence of enzalutamide. In addition, we show that enzalutamide resistant cells are insensitive to bicalutamide but retain considerable sensitivity to abiraterone. Mechanistically, enzalutamide resistance was accompanied by increased AR and AR-V7 mRNA and protein expression as well as AR gene amplification, while no additional AR mutations have been identified.
Keywords: mutace; regulace genové exprese u nádorů; Drug Resistance, Neoplasm; proliferace buněk; fenylthiohydantoin; Cell Line, Tumor; Gene Expression Regulation, Neoplastic; Phenylthiohydantoin; lidé; Tosyl Compounds; chemorezistence; signální transdukce; Mutation; Androstenes; nádory prostaty; Signal Transduction; Prostatic Neoplasms; Humans; androsteny; Male; nitrily; Nitriles; Cell Proliferation; tosylové sloučeniny; Receptors, Androgen; Cell Survival; mužské pohlaví; viabilita buněk; androgenní receptory; Anilides; nádorové buněčné linie; anilidy